Removable Prosthesis with Extra Coronal Attachment for the Management of Distal Extension Case: A Case Report - Thapa, Dipak; Shrestha, P. (Journal of Nepalese Prosthodontic Society, 2018)
Even though dental attachments have a long successful history, many of the dental practioners are unaware about its benefits in daily clinical practice. It highly improves the comfort, aesthetic, function and patient satisfaction, especially in the patients with long span edentulism where implants and fixed partial denture (FPD) are not indicated and cast partial dentures are barely satisfactory. This case report describes the clinical and the laboratory steps for prosthetic rehabilitation of a patient with maxillary distal extension partially edentulism with cast partial denture using Preci Vertex attachments.